SoxF factors induce Notch1 expression via direct transcriptional regulation during early arterial development - Chiang, I; Fritzsche, M; Pichol-Thievend, C; Neal, A; Holmes, K; Lagendijk, A; Overman, J; D’Angelo, D; Omini, A; Hermkens, D; Liu, K; Ratnayaka, I; et al. (Company of Biologists, 2017)
Arterial specification and differentiation are influenced by a number of regulatory pathways, encompassing numerous growth factors, signaling molecules and transcription factors. While it is known that the Vegfa-Notch cascade plays a central role in this biological process, the transcriptional hierarchy controlling arterial specification has not been fully delineated. To elucidate the direct transcriptional regulators of Notch receptor expression in arterial endothelial cells, we used histone signatures, DNaseI hypersensitivity and ChIP-seq data to identify enhancers for the human NOTCH1 and zebrafish notch1b genes. These enhancers were able to direct arterial endothelial cell-restricted expression in transgenic models. Genetic disruption of SOXF binding sites clearly established a requirement for members of the SOXF group of transcription factors (SOX7,-17 and-18) to drive these enhancers activity in vivo. Further, endogenous deletion of the notch1b enhancer led to a significant augmentation of arterio-venous defects in notch-pathway deficient zebrafish. Loss of SoxF function revealed that these factors are necessary for the activity of NOTCH1 and notch1b enhancers, and for correct endogenous Notch1 gene transcription. These findings therefore position SOXF transcription factors directly upstream of Notch receptor expression during the acquisition of arterial identity in vertebrates.